(untitled) (Research, Society and Development, 2022)
Objective: Based on the Item Response Theory, to elaborate a reduced scale, from the Questionnaire on Knowledge of the Human Immunodeficiency Virus, in the Deprived of Liberty Population. Methodology: Validation study with 571 men and women deprived of their liberty, closed regime, from the 5th Regional Penitentiary South Police Station. By Self-Applied Human Immunodeficiency Virus Knowledge Questionnaire. Analyzed by Item Response Theory, dimensionality by exploratory and confirmatory factor analysis. Internal consistency assessed by Crombach’s alpha and the relevance of each item calculated by point biserial correlation. The two-parameter logistic model and identification of the anchor items, according to the level of theta knowledge, made it possible to organize the reduced scale. RESULTS: 571 respondents, 90% men, mean age 32 years, 63% white skin, 61%, no partner and mean schooling 7 years. The original scale items (n=43) with the best psychometric fit were kept. 4 items excluded. The final scale consisted of 39 items, four levels of knowledge about Human Immunodeficiency Virus, positioned in the 45th to 60th percentile range. Of these, a greater number of items was obtained at level 50 (average), suggesting that the instrument is suitable for evaluating individuals with average knowledge on the subject. Conclusion: The reduced scale of the questionnaire on Knowledge of the Human Immunodeficiency Virus, with a one-dimensional model, remained with 39 dichotomous items, with discriminative ages and with median difficulty for the population studied.